COGNITIVE PATTERNS AND UNDERSTANDING OF MATHEMATICAL CONCEPTS IN INTEGRATED PROBLEM-BASED LEARNING OF AMBON CULTURE - Patma Sopamena; Ajeng Gelora Mastuti; Sakinah Econ Kabiran; Ekawati Kadir; Mar’i Mardas (MATEMATIKA DAN PEMBELAJARAN, 2026)
This study aims to analyze students' cognitive patterns and understanding of mathematical concepts in problem-based learning that integrates ethnomathematics, in comparison with materials that do not. This study uses a mixed method with quantitative data in the form of concept comprehension scores and qualitative data in the form of code networks and concept maps that represent the relationship between the learning process, the Ambon cultural context, and students' affective responses. The population and sample are 149 junior high school students in Ambon City, and among them, 8 students were taken as subjects. The instruments of this research consist of: GEFT based on   Ambon Cultural Illustration, concept comprehension tests, observation sheets, and interview guidelines. Data analysis uses quantitative and qualitative analysis using NVivo. The results showed that students with field independent (FI) cognitive styles achieved an average concept comprehension score of 86.6, higher than field dependent (FD) students with an average of 79.2. In addition, the cultural context of Ambon (barter system and Baileo houses) significantly helped FD students in concretizing the concept of comparison through scaffolding and group discussions. Furthermore, student affective engagement is increased through ethnomathematical integration. Keywords: Ambon Culture, Cognitive Patterns, Concept Understanding, ethnomathematics, Problem-Based Learning